Multiple repeat caesarean section in the UK: incidence and consequences to mother and child. A national, prospective, cohort study. Issue 1 (24th October 2012) - Cook, JR; Jarvis, S; Knight, M; Dhanjal, MK
<x xml:space="preserve">Abstract</x> Objective To estimate the incidence of multiple repeat caesarean section (MRCS) (five or more) in the UK and to describe the outcomes for women and their babies relative to women having fewer repeat caesarean sections. Design A national population‐based prospective cohort study using the UK Obstetric Surveillance System (UKOSS). Setting All UK hospitals with consultant‐led maternity units. Population Ninety‐four women having their fifth or greater MRCS between January 2009 and December 2009, and 175 comparison women having their second to fourth caesarean section. Methods Prospective cohort and comparison identification through the UKOSS monthly mailing system. Main outcome measures Incidence, maternal and neonatal complications. Relative risk, unadjusted (OR) and adjusted (aOR) odds ratio estimates. Results The estimated UK incidence of MRCS was 1.20 per 10 000 maternities [95% confidence interval (CI), 0.97–1.47]. Women with MRCS had significantly more major obstetric haemorrhages (>1500 ml) (aOR, 18.6; 95% CI, 3.89–88.8), visceral damage (aOR, 17.6; 95% CI, 1.85–167.1) and critical care admissions (aOR, 15.5; 95% CI, 3.16–76.0), than women with lower order repeat caesarean sections. These risks were greatest in the 18% of women with MRCS who also had placenta praevia or accreta. Neonates of mothers having MRCS were significantly more likely to be born prior to 37 weeks of gestation (OR, 6.15; 95% CI, 2.56–15.78) and therefore had higher rates of complications and admissions. Conclusions MRCS is associated with greater maternal and neonatal morbidity than fewer caesarean sections. The associated maternal morbidity is largely secondary to placenta praevia and accreta, whereas higher rates of preterm delivery are most likely a response to antepartum haemorrhage.